A Healthier Distance? Spatial Proximity to Everyday Amenities and Self‐Rated Health among Older Adults in the Northern Netherlands - Sattari, Zeinab; Vogt, Tobias; Meijering, Louise; Weitkamp, Gerd (Tijdschrift voor economische en sociale geografie, 2025)
This study investigates the association between the proximity of home to various everyday life amenities and self‐rated health (SRH) among 7,226 older adults who participated in the Lifelines health survey. Our results show that SRH was significantly higher for participants living farther from grocery shops and closer to healthcare places. We also found that not being female, living alone, having a paid job, having a high level of education (especially in less urban areas) and higher income levels were significantly associated with higher SRH. In conclusion, while proximity to amenities is important for healthy ageing in place, the association between the two is not always positive. Additionally, spatial policies need to pay special attention to the needs of more vulnerable and deprived older groups.